Catabolic effect of dexamethasone in the preterm baby. Issue 1 (January 1992) - Brownlee, K G; Ng, P C; Henderson, M J; Smith, M; Green, J H; Dear, P R
Abstract : Most babies treated with dexamethasone for bronchopulmonary dysplasia exhibit an appreciable rise in the blood urea concentration, from a mean of 2.3 mmol/l before steroid to a mean of 7.1 mmol/l after. In order to discover whether this was primarily the result of increased protein catabolism, nitrogen balance studies before and after the start of dexamethasone were performed and a mean deficit in nitrogen retention of 158 mg/kg/24 hours was found. Similarly the urinary 3-methylhistidine (3MH):creatinine ratio before and after the commencement of dexamethasone treatment in a group of preterm babies was measured. It was found that there was a substantial increase in 3MH excretion after dexamethasone: from a mean 3MH:creatinine ratio of 46 in the week before steroids to a mean ratio of 77 in the week after. As 3MH emanates almost exclusively from the breakdown of actin in skeletal muscle cell, this finding implies the loss of muscle tissue. It was also found that the babies were in less positive nitrogen balance after dexamethasone, to a degree which is significant relative to their protein reserves. The long term consequences of a period of increased catabolism are not yet known but the authors suggest caution in the use of dexamethasone, at least in babies with milder degrees of bronchopulmonary dysplasia in whom the ratio of benefit to risk may be less favourable.